Incidence and traditional management of snakebites in the Bofidji-Bolenge Grouping, Wangata Commune, Mbandaka City, Democratic Republic of the Congo - Blaise Engomba Mokekola; Koto-; Assumani Idrissa Zabo; Guy Bayeli Ilumbe; Aristarque Bulambo Mulonda; Monizi Mawunu; Gires Mboyo Engomba; Colette Ashande Masengo; Arsène Bokulu (Orapuh, Inc., 2024)
Introduction Snakebitesrepresent a significant public health problem, particularly in rural and remote areas where access to medical facilities and antivenoms is limited. Purpose The purpose of this study was to investigate the incidence and traditional management of snakebites in the Bofidji-Bolenge Grouping, Wangata Commune, Mbandaka City, Democratic Republic of the Congo. Methods The study area includes sites such as Mbandaka ea Mbula, Lokekya, Bopenzola, and Ikengo. The survey, conducted from January 2019 to December 2020, focused on mainland populations. A mixed-methods approach was employed, combining quantitative surveys of households and qualitative interviews with local residents, including doctors, herbalists, traditional healers, snakebite victims, their caregivers, and land chiefs. Questionnaires were administered to gather comprehensive data on snakebite occurrences and their management within the community. Results Epidemiologicalinvestigations recorded 1,569 pathological cases, with 780 men (49.71%) and 789 women (50.29%) affected. Pregnant women were particularly impacted, comprising 15.36% of cases. Men with pregnant partners at the time of the bite represented 12.94%. Men and women, in general, accounted for 11.92% and 11.66% of cases, respectively. Children were also affected, with boys at 7.52% and girls at 4.33%. The highest annual prevalence was at the Lokekya site (4.31%). The study identified 37 medicinal plants used in traditional treatments for snakebites and envenomations. Conclusion The study underscores the pivotal role of traditional medicine in addressing public health challenges, particularly in managing snake bites through indigenous plant treatments and the expertise of traditional healers. To improve snakebite management in the DRC, it is recommended to conduct phytochemical analyses of the 37 identified medicinal plants to verify their active compounds.